Strategi Penguatan Identitas Produk dan Akses Pasar Usaha Mikro, Kecil, dan Menengah (UMKM) Raja Basreng: Studi Kasus: KKN Kelompok 4 di Kp. Tapos Udik RT. 002/ RW. 002 Desa Tapos 1 Kecamatan Tenjolaya Kabupaten Bogor - Somantri, Fikri Indriana; Novita, Evi; Supriyatna, Rio Kartika; Junaedi, Dedi; Wijaya, Siska Putri; Iskandar, Nandang; Rahmawati, Dian; Putri, Sardiani; Fikri, M. Chairil; Murtafiah, Fifih (El-Mujtama: Jurnal Pengabdian Masyarakat, 2025)
UMKM play a central role in driving local economies, yet they often face challenges in building a strong product identity and effectively expanding market access. This study aims to identify and analyze strategies that can be implemented to strengthen product identity and market access for UMKMs, using a case study of the "Raja Basreng" UMKM in Tapos 1 Village, Tenjolaya District, Bogor Regency. The research employed a descriptive qualitative approach, collecting data through field observations, direct interviews with UMKM owners, and documentation of production and marketing activities. The results indicate that Raja Basreng possesses strong product flavor and name characteristics, but has not yet developed a comprehensive branding strategy. The product identity remains latent, not optimally conveyed through visual elements (packaging, logo, and design), narrative (product story), or consumer experience. Furthermore, market access remains geographically limited due to the dominance of offline sales and minimal utilization of digital channels such as social media or marketplaces. This study recommends the importance of an integrated branding approach with a digital marketing strategy to effectively convey product value and reach a broader market. Awareness of the importance of building product identity is not merely an aesthetic necessity, but a long-term investment in building image, consumer loyalty, and sustainable competitiveness. The implications of this research not only impact the economic empowerment of UMKMs but also open up new opportunities for developing local potential based on narrative and technological strengths.